2007
DOI: 10.2478/s11535-007-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor 2 is emerging as a major player in the control of iron metabolism

Abstract: Our knowledge of mammalian iron metabolism has advanced dramatically over recent years. Iron is an essential element for virtually all living organisms. Its intestinal absorption and accurate cellular regulation is strictly required to ensure the coordinated synthesis of the numerous iron-containing proteins involved in key metabolic processes, while avoiding the uptake of excess iron that can lead to organ damage. A range of different proteins exist to ensure this fine control within the various tissues of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…11 We present here the first evidence that the same activation is operating in hepatocytes and that ERK activation is necessary for holotransferrin-induced hepcidin gene expression. Interestingly, we also showed that holotransferrin regulates hepcidin mRNA concentrations through a HJV/BMP dependent pathway since the effect of holotransferrin was lost in the presence of noggin and BMP2/4 antibodies.…”
Section: Discussionmentioning
confidence: 65%
“…11 We present here the first evidence that the same activation is operating in hepatocytes and that ERK activation is necessary for holotransferrin-induced hepcidin gene expression. Interestingly, we also showed that holotransferrin regulates hepcidin mRNA concentrations through a HJV/BMP dependent pathway since the effect of holotransferrin was lost in the presence of noggin and BMP2/4 antibodies.…”
Section: Discussionmentioning
confidence: 65%